The Role of Human Resources in Improving the Company's Financial Performance - Syukri, Andi Muhammad; Malik, Tajuddin; Sandra, Kurniawati; Mattalatta, Mattalatta; Ansar, Ansar; Farida, Umi (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study examines the relationship between strategic human resource (HR) practices and financial performance, focusing on optimizing HR investments for sustainable economic success. The research addresses HR practices such as training, competency development, and reward systems in enhancing organizational outcomes. A systematic literature review (SLR) methodology synthesized findings from recent industry studies. This approach allowed for an integrative analysis of theoretical frameworks, including the Resource-Based View (RBV) and Agency Theory, to contextualize the impact of strategic HR practices on financial performance. The study highlights the significant influence of HR practices on organizational productivity, operational efficiency, and cost reduction. Practices like Green Human Resource Management (GHRM) enhance sustainability and improve reputation and financial outcomes. Integrating technology, such as data analytics and performance tracking systems, was identified as a crucial enabler for decision-making and resource optimization. The findings also emphasize aligning HR planning with organizational strategies to ensure coherent and effective workforce management. This research contributes to academic literature and practical applications by offering actionable strategies for optimizing HR investments. It provides a roadmap for managers to implement innovative HR practices that align with business objectives, foster sustainability, and enhance competitiveness. This study's limitations, including its reliance on secondary data, suggest avenues for future empirical research to validate and expand on these findings.